(untitled) (JED (Jurnal Etika Demokrasi), 2020)
Abstract. Character education is about educating for character. In other words, it is leveraging education to encourage the development of character for students, and other stakeholders, in the educational context (Murray et al., 2019). This study aims to investigate the implementation of the disciplinary character education of cadets regarding time discipline, to obey the rules, discipline of behavior and worship in PIP Makassar. This research used qualitative descriptive research method. Techniques of data collection were observation, interviews and questionnaires. Population was cadets in the first Semester, second semester, fourth Semester and eighth semester cadets Diploma IV or Bachelor, deck, engine and port shipping management in PIP Makassar. A total population was 1291 respondents (cadets). The number of samples was 130 respondents (cadets) through stratified random sampling technique that is simple random sampling.The implementation of disciplinary character education in PIP Makassar had been running well based on the pattern of cadets parenting and set in the rules of order cadets, the cadets discipline levels were good category based on the results of questionnaire data, it was just supervision still needed to be improved and used the pattern or the method of positive habituation regarding discipline and obedience to the rules, because building disciplinary character education for cadets was hard, it needed an extra process starting from the educational institutions environment by implementing a quality system and positive environment based on the term of characters education. To inhibit undisciplinary had to implement academic sanctions or punishment that deterrent cadets who often made mistakes or acts of disciplinary violations repeatedly so that they can teach lessons for cadets who violate and other cadets who did not violate disciplinary actions. Keywords: character education, discipline, cadets Pendidikan karakter adalah tentang mendidik karakter. Dengan kata lain, memanfaatkan pendidikan untuk mendorong pengembangan karakter bagi siswa, dan pemangku kepentingan lainnya, dalam konteks pendidikan (Murray et al., 2019). Penelitian ini bertujuan untuk mengetahui implementasi pendidikan karakter disiplin taruna tentang disiplin waktu, untuk mematuhi aturan, disiplin perilaku dan ibadah di PIP Makassar. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Teknik pengumpulan data adalah observasi, wawancara dan kuesioner. Populasi adalah kadet di semester pertama, semester kedua, semester keempat dan semester delapan Diploma IV atau Sarjana, Prodi Dek, Mesin dan Manajemen di PIP Makassar. Total populasi adalah 1.291 responden (taruna/i). Jumlah sampel adalah 130 responden (taruna/i) melalui teknik stratified random sampling yaitu simple random sampling. Implementasi pendidikan karakter kedisiplinan di PIP Makassar telah berjalan dengan baik berdasarkan pola pengasuhan taruna dan ditetapkan dalam aturan taruna/i, tingkat kedisiplinan taruna/i adalah kategori baik berdasarkan hasil data kuesioner, hanya saja pengawasan masih diperlukan untuk ditingkatkan dan menggunakan pola atau metode habituasi positif mengenai disiplin dan kepatuhan terhadap aturan, karena membangun pendidikan karakter disiplin untuk taruna/i sulit, diperlukan proses ekstra mulai dari lingkungan lembaga pendidikan dengan menerapkan sistem kualitas dan lingkungan positif berdasarkan istilah karakter pendidikan. Untuk menghambat ketidakdisiplinan harus menerapkan sanksi atau hukuman akademik yang menghalangi taruna/i yang sering melakukan kesalahan atau tindakan pelanggaran disipliner berulang kali sehingga mereka dapat mengajarkan taruna/i yang melanggar dan taruna/i lainnya yang tidak melanggar tindakan disipliner. Kata Kunci: Pendidikan karakter, disiplin, taruna/i